AI-based Interventions for Mental Health: Current Scenario and Future Prospects - Kumar, Abhishek; Ranjan, Nihar M; Shah, Siddhartha Kr; Sarkar, Neha (Nepal Journal of Neuroscience, 2001)
Modern artificial intelligence (AI), and machine learning in particular, is being used to create prediction, diagnostic, and treatment solutions for mental health care in light of the growing popularity of digital approaches to mental health. Due to their prevalence, depression and anxiety represent the two main mental health conditions that have been the subject of most digital phenotyping research. Chatbots have been used for mental health issues since the 1990s, but their effectiveness remains unknown due to their early stages, though some early studies suggest improvement in anxiety and depression. ChatGPT and other AI platforms have potential applications in various industries, including mental health, and are rapidly expanding. Artificial Intelligence (AI) has the potential to improve accessibility and reduce costs for mental health services by utilizing smartphones. With the increasing use of smartphones, AI systems can be used to diagnose mental illnesses, identify them at a prodromal stage, personalize medicines, and empower individuals in their care. However, AI must address challenges such as bias, privacy, transparency, and ethical concerns. These goals reflect human wisdom and the stronger connection between individual and community well-being than IQ. In the future, AI may develop technology that enables more empathetic and morally upstanding care for various groups, reflecting the importance of human wisdom in addressing mental health issues. More work is required to bridge the gap between clinical treatment and AI in mental health research, while caution must be exercised to avoid overinterpreting early findings.